Solvent-Dependent Catalytic Behavior of Telluride-Containing Guest Artificial Glutathione Peroxidase Using Cumene Hydroperoxide and 3-Carboxyl-4-nitrobenzenethiol as Substrates - Jiao, S.F.; Yin, Y.Z.; Zhang, R.R.; Zhong, S.M.; Wang, X.Q.; Zhang, L.; Yang, L. (Asian Journal of Chemistry, 2015)
To reveal the solvent-dependent catalytic behaviour of a hydrophobic telluride-containing guest artificial glutathione peroxidase (ADA-Te-OH), the catalytic rates were investigated using cumene hydroperoxide and 4-nitrobenzenethiol as substrates. Herein, ethanol, DMSO, DMF and CH3CN were selected as the co-solvents in the determination of catalytic rates. Significantly, the typical solvent-dependent catalytic behaviour of ADA-Te-OH was observed. Especially, the higher catalytic rate was observed when polar protic solvent (ethanol) was used compared with other co-solvents. It suggested that polar protic solvent was the appropriate co-solvent for the assay of catalytic activity of hydrophobic artificial glutathione peroxidase. This study well for the understanding of the catalytic behaviour of hydrophobic guest artificial glutathione peroxidase.